Analysis Of Market Anomalies For Stock Returns At Lq45 Companies In Indonesia - Faizal Ridwan Zamzany; Rizka Utami Purwaningsih; Ummu Salma Al Azizah (Agregat: Jurnal Ekonomi dan Bisnis, 2020)
This study examines the effects of the market anomaly on Indonesia's LQ45 companies' stock returns. This research uses descriptive and comparative methods with a quantitative approach. Data processing and analysis techniques include quantitative analysis in multiple linear regression analysis without interception (through multiple regression). The variables used in this study are dummy variables. The dependent variable of this study is daily stock returns. The results showed that The Day of The Week Effect affected stock returns. The Week Four Effect variable shows that the lowest return (negative) on Monday in LQ45 is not concentrated on Monday the last two weeks of each month. The Monday Effect variable indicates that it is not only negative Friday returns that drive negative Monday returns. The Rogalsky Effect variable indicates there was no Rogalsky Effect in April.